2019
DOI: 10.1111/jog.14063
|View full text |Cite
|
Sign up to set email alerts
|

Application of ‘no‐touch’ hysteroscopy (vaginoscopy) for the treatment of abnormal uterine bleeding in adolescence

Abstract: Aim: This article retrospectively analyzed the efficacy and safety of vaginoscopy in the treatment of adolescent abnormal uterine bleeding (AUB) in 204 cases of AUB. Method: From patients with intact hymen who were admitted to our hospital due to AUB received vaginoscopy, and vaginoscopy did not damage the hymen. In this study, 4.5 mm and 6.5 mm hysteroscopy were used with a pumping fluid pressure of 100-120 mm Hg and a flow rate of 400 mL/min. All 204 vaginoscopy was successfully completed in intravenous anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…After a randomized controlled trial, Smith et al [ 8 ] found vaginoscopy to be quicker to perform, less painful to patients, and more successful than standard hysteroscopy. Vaginoscopy, a “no-touch” approach, can be used not only to perform endometrial biopsy and remove foreign bodies in the vagina but also to meet the hopes of patients and their families of not damaging the hymen and reducing pain[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…After a randomized controlled trial, Smith et al [ 8 ] found vaginoscopy to be quicker to perform, less painful to patients, and more successful than standard hysteroscopy. Vaginoscopy, a “no-touch” approach, can be used not only to perform endometrial biopsy and remove foreign bodies in the vagina but also to meet the hopes of patients and their families of not damaging the hymen and reducing pain[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuckahoe has the effect of improving water permeability, invigorating the spleen and calming heart. Scutellaria charcoal has the effects of clearing heat, dampness, relieving fire and detoxifying (23). Perimenopausal AUB patients are often accompanied by varying degrees of anemia, so this prescription can repair the patient's uterus and replenish blood and qi.…”
Section: Comparison Of Vegf Expression Levels Between the Two Groups ...mentioning
confidence: 99%
“…It is recommended to adopt this painless, non-traumatic and innovative technique [2]. This technique is also used for women with intact hymen and adolescent girls with abnormal vaginal discharge and abnormal uterine bleeding without damaging the intact hymen [3,4]. This no-touch technique is more acceptable to patients, and they are more comfortable getting this procedure done in an office setting.…”
Section: Vimee Bindramentioning
confidence: 99%